Prevalence of Stroke and Associated Factors in a Middle-aged and Older Chinese Population: A Cross-sectional Study - Juan Guo; Qingmin Guo; Yuzhen Chen; Jinmei Zou; Hanjia Gao (Cardiology Discovery)
Abstract. Objective:. Elderly individuals are at high risk for stroke. With China transitioning into an aging society, it is essential to implement measures to prevent stroke in the middle-aged and elderly. This study aimed to investigate the prevalence and associated factors of stroke in middle-aged and older Chinese individuals using national survey data from the China Health and Retirement Longitudinal Study. Methods:. This cross-sectional study used data from the 2015 China Health and Retirement Longitudinal Survey. Participants without complete data on stroke and its associated factors—including demographics, health behaviors, and disease-related factors—were excluded. Independent samples t-test and χ2 test were used to examine differences in associated factors between the stroke and non-stroke groups. Variables with P-values ≤0.1 in all univariate comparisons were included in the final binary logistic regression model to identify the independent factors associated with stroke. Results:. A total of 11,969 participants were included in this study. The prevalence of stroke in middle-aged and older individuals in China was 2.170%. The most significant factors associated with stroke included smoking (odds ratio (OR): 1.471, 95% confidence interval (CI): 1.132–1.913), alcohol consumption (OR: 0.548, 95%CI: 0.405–0.743), nap time ≥30 min and <60 min (OR: 0.502, 95%CI: 0.296–0.851), nap time ≥60 min and <90 min (OR: 0.703, 95%CI: 0.505–0.978), hypertension (OR: 3.310, 95%CI: 2.515–4.357), dyslipidemia (OR: 1.874, 95%CI: 1.446–2.428), and diabetes (OR: 1.424, 95%CI: 1.052–1.927). Conclusion:. This study reveals a high prevalence of stroke in middle-aged and older people in China. Several factors, including smoking, alcohol consumption, nap time, hypertension, dyslipidemia, and diabetes, were identified as significant associated factors of stroke prevalence in this population. These findings can inform the development of stroke prevention strategies and health planning for middle-aged and older adults and provide insights for future research.